PENINGAKATAN KAPASITAS NELAYAN DALAM MENDUKUNG PENANGKAPAN IKAN BERKELANJUTAN DI PAAP TELUK KOLONO PROVINSI SULAWESI TENGGARA - Kamri, Syamsul; Hamid, Abdul; Patadjai, Andi Besse; Patadjai, Rahmad Sofyan; Balubi, Abdul Muis (Bina Bahari, 2023)
The management of fisheries access areas is one form of ecosystem-based fisheries management, which integrates marine protected area activities with controlled fishing activities carried out by local fishermen. The objective of sustainable fishing activities in the Kolono Bay Fisheries Access Area is to enhance the capacities of both the local fishermen and the PAAP management. This initiative involves the participation of 15 managing fishermen from five villages: All located in the Kolono Bay area. The project commences with the formation of groups, followed by discussion forums group, guided by a facilitator from RARE Indonesia Sultra. The DFG sessions were held twice, each with distinct themes: (1) issues and challenges encountered by fishermen during fishing activities in Kolono Bay, and (2) concerns related to climate change. Participants exhibited great enthusiasm throughout the engagement, as evidenced by the active sharing of the challenges they have faced concerning their fishing activities in Teluk Kolono during the FGD sessions. The outreach material was presented in simple language to ensure participants' comprehension. In general, it can be concluded that the information provided during this engagement has the potential to enhance the capacities of fishermen engaged in PAAP management in Teluk Kolono to support sustainable fishing.